A Blockchain-Based Tokenization Approach to Empower Farmers and Youth in Smart Agriculture (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Smart agriculture has witnessed significant advancements through the integration of digital technologies; however, traditional agricultural trade systems still suffer from issues such as lack of transparency, unfair pricing, and dependence on intermediaries.These challenges often limit farmer profitability and reduce youth participation in agriculture. To address these issues, this article presents a blockchain-based tokenization approach designed to enable secure, transparent, and decentralized agricultural trade.In the proposed system, agricultural produce is represented as digital tokens on a blockchain network, allowing farmers to tokenize crop batches and directly engage with buyers through smart contracts. The use of blockchain ensures immutability, traceability, and trustless transactions, while smart contracts automate ownership transfer and payment settlement without the need for third-party intermediaries.The framework promotes fair trade practices, enhances trust among stakeholders, and encourages youth involvement by introducing digital ownership and decentralized transaction mechanisms. The proposed approach demonstrates how blockchain-enabled tokenization can support sustainable smart agriculture and create an inclusive digital agricultural ecosystem.